Evaluation of The Program of Providing Additional Feeding (PMT) of Local Food for Pregnant Women at The Padangmatinggi Community Health Center, Padangsidimpuan City - Azizah Ameliah; Lucy Widasari; Zuraidah Nasution (JURNAL KESMAS DAN GIZI (JKG), 2026)
Nutritional problems among pregnant women, such as Chronic Energy Deficiency (CED) and anemia, remain significant challenges in efforts to reduce maternal and infant mortality rates in Indonesia. In response to this issue, the Padangmatinggi Public Health Center in Padangsidimpuan City has implemented a Local Food-Based Supplementary Feeding Program (PMT) as a specific nutrition intervention. However, the effectiveness of this program has yet to be comprehensively evaluated. This study aims to assess the implementation of the PMT program using a systems approach, covering the components of input, process, and output.This research adopts a descriptive qualitative method with a case study design. Data were collected through in-depth interviews, observation, and document review involving seven key and supporting informants. The findings indicate that input components—such as human resources, infrastructure, and budget support—are adequate and support the implementation of the program. The intervention process followed established procedures, including the identification of CED-targeted pregnant women based on MUAC <23.5 cm, distribution of supplementary food by health workers and community health volunteers, and routine nutritional status monitoring. The program’s output showed improvements in the nutritional status of pregnant women with CED, as evidenced by increases in body weight and mid-upper arm circumference.Nevertheless, the program faces challenges, particularly in the limited number of community health volunteers and reliance on central government funding, which could hinder its sustainability. Therefore, strategies are needed to strengthen implementation capacity through regular training and the development of local food education modules, along with enhanced efficiency in monitoring systems through digitalization. This study is expected to serve as a reference for policy-making in maternal nutrition interventions at both local and national levels.